(untitled) (Research, Society and Development, 2020)
Transparency aims to ensure the publication of government data and information, making it available to all citizens, contributing to the control and improvement of the management of public resources. This information must be understandable by all citizens, so that individuals can observe what has been done and give their opinion. These things are determined in the Access to Information Law, which provides for the disclosure of information. Thus, the present study aims to analyze the citizens who access the municipal public transparency portals and how they perceive them. A survey was carried out with 264 individuals from the state of Rio Grande do Sul. As data analysis techniques, the t test, ANOVA, Pearson’s chi-square and factor analysis were used. The results show that the majority of citizens do not access the municipal transparency portal. Based on factorial analysis, four factors were formed. The perception of citizens aged 26 to 35 years is higher than those aged 36 to 45 years in relation to the interaction factor, and the perception of employees of a private company is greater than public officials regarding the resources factor. Therefore, the fact that the majority of respondents do not access the municipalities’ transparency portal demonstrates that much still needs to be done in order for society to participate effectively in the municipal public transparency process.